2011
DOI: 10.1186/1472-6904-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Price, familiarity, and availability determine the choice of drug - a population-based survey five years after generic substitution was introduced in Finland

Abstract: BackgroundMandatory generic substitution (GS) was introduced in Finland at the beginning of April 2003. However, individual patients or physicians may forbid the substitution. GS was a significant change for Finnish medicine users. It was thought it would confuse people when the names, colors, packages, etc., changed. The purpose of this study was to explore what medicine-related factors influence people's choice of prescription drugs five years after generic substitution was introduced in Finland.MethodsA pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
(13 reference statements)
2
17
1
Order By: Relevance
“…These studies range from qualitative assessment of perceptions in specific patient cohorts [59] to general lay/consumer knowledge [60,61], versus knowledge of professionals [62,63]. Many of these studies focus on the influence of relative cheapness on perceptions and use of generic medicines [64,65]. Some publications have shown that consumers felt that a generic medicine did not work either as effectively, or at all, in comparison to when they were taking the originator medicine [66].…”
Section: A Brief History Of Pharmaceutical Regulationsmentioning
confidence: 99%
“…These studies range from qualitative assessment of perceptions in specific patient cohorts [59] to general lay/consumer knowledge [60,61], versus knowledge of professionals [62,63]. Many of these studies focus on the influence of relative cheapness on perceptions and use of generic medicines [64,65]. Some publications have shown that consumers felt that a generic medicine did not work either as effectively, or at all, in comparison to when they were taking the originator medicine [66].…”
Section: A Brief History Of Pharmaceutical Regulationsmentioning
confidence: 99%
“…The patients who had substituted their medicines had not noticed any differences between the previously used and substituted medicines. Price, availability and familiarity were the three most important factors that influenced their choice of medicines, whereas the external characteristics, for instance the colour and shape of the tablet/capsule or the appearance of the package, were not significant characteristics for people …”
Section: Generic Substitution In Finlandmentioning
confidence: 99%
“…Consequently, it is important to know which prescription medicine-related factors affect patients' choices in order to develop and provide information for patients to support their decision making. Although a large number of studies have examined GS from different perspectives, only a few have explored prescription medicine-related factors that affect patients' choice of prescription medicine [8,9,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%